Assertiveness skills - Alberti, Robert (Boston, MA : Allyn and Bacon, 2002)
In this tape, Dr. Robert Alberti teaches a group of participants how to practice assertive behaviors with or without words, how to'say no' clearly and directly, how to implement a step-by-step process for becoming assertive, and how to overcome obstacles to assertiveness
Moderator by John Carlson, Judy Lewis
Keywords: Assertiveness (Psychology).